Humoral Immune Response to SARS-CoV-2 Vaccination after a Booster Vaccine Dose in Two Kidney Transplant Recipients with Fabry Disease and Variable Secondary Immunosuppressive Regimens - Bernea, Lavinia; Ailioaie, Oana R; Benhamouda, Nadine; Tartour, Eric; Germain, Dominique P (Vaccines, 2021)
The urgent need to fight the COVID-19 pandemic has accelerated the development of vaccines against SARS-CoV-2 and approval processes. Initial analysis of two-dose regimens with mRNA vaccines reported up to 95% efficacy against the original strain of the SARS-CoV-2 virus. Challenges arose with the appearance of new strains of the virus, and reports that solid organ transplant recipients may have reduced vaccination success rates after a two-dose mRNA vaccination regimen encouraged health authorities to recommend a booster in immunocompromised patients. Fabry disease is an X-linked inherited lysosomal disorder, which may lead to chronic end-stage renal disease. We report on two patients with advanced Fabry disease, renal graft and adjunctive immunosuppressive therapies who exhibited variable humoral vaccination-related immune responses against SARS-CoV-2 after three vaccine doses. The first patient developed mild COVID-19 infection, while the second patient did not seroconvert after three shots of an mRNA vaccine. Both cases emphasize that patients with Fabry disease and renal graft are susceptible to develop a weak response to COVID-19 vaccination and highlight the importance of maintaining barrier protection measures. Vaccination of family members should be encouraged to lower the risk of viral transmission to immunocompromised, transplanted patients, including vaccinated ones.
Keywords: vaccine; renal transplant; COVID-19; Fabry disease